An Autopsied Case of Malignant Sarcomatoid Pleural Mesothelioma in Which Chest Pain Developed Several Months Earlier without Abnormality on Imaging - Yaguchi, Daizo (Case Rep Oncol, 2015)
The patient experienced chest pain for about 7 months, but a diagnosis could not be made until after death. He was diagnosed with malignant sarcomatoid pleural mesothelioma on autopsy. In this case report, difficult aspects of the diagnosis are discussed. The 70-year-old Japanese man was a driver who transported ceramic-related products. Right chest pain developed in July 2013, but no abnormality was detected on a chest computed tomography (CT) performed in September 2013, and the pain was managed as right intercostal neuralgia. A chest CT performed in late October 2013 revealed a right pleural effusion, and the patient was referred to our hospital in early November 2013. Thoracentesis was performed, but the cytology was negative, and no diagnosis could be made. Close examination was postponed because the patient developed a subarachnoid hemorrhage. He underwent (18)F-fluorodeoxyglucose positron emission tomography ((18)F-FDG PET) after discharge from the neurosurgery department, and extensive right pleural thickening and (18)F-FDG accumulation in this region were observed. Based on these findings, malignant pleural mesothelioma was suspected, and a thoracoscopy was performed under local anesthesia in early December 2013, but no definite diagnosis could be made. The patient selected best supportive care and died about 7 months after the initial development of right chest pain. The disease was definitively diagnosed as malignant sarcomatoid pleural mesothelioma by a pathological autopsy. When chronic chest pain of unknown cause is observed and past exposure to asbestos is suspected, actions to prevent delay in diagnosis should be taken, including testing for suspicion of malignant pleural mesothelioma.